Students' States of Matter Achievement : Reasoning Ability or Instructional approach? - Alhassan Libata, Ibrahim; Mohd Norawi Ali; Hairul Nizam Ismail (Asia Pacific Journal of Social Science Research, 2022)
The present study is aimed to determine if there is any relationship between cognitive developmental level and states of matter achievement. A total of 39 Form Two students constitutes the sample of the study. The subjects were tested at a two-time interval (phase1, phase2). The study was conducted in two randomly selected government day secondary schools. Lawson Classroom Test of Scientific Reasoning (LCTSR) and States of Matter Achievement Test (SMAT) were administered to participants to gauge their cognitive level and states of matter achievement. One-way analysis of covariance (ANCOVA) was conducted to investigate the effect of cognitive level on students' states of matter transformation. The student's cognitive level is the independent variable (concrete and formal), the dependent variable is the multiple-choice test on states of matter transformation. Students' pre-test scores were used as a covariate. The result showed that while there is a mean different between concrete and formal students (concrete=51.45 and formal 54.59), however, there was no statistically significant effect of cognitive level on student states of matter achievement F(1, 36)= 3.156, P>0.05, also the covariate (pre-test) was not significantly related to participant's states of matter achievement F(1, 36)= 0.90, p>.05.